A tributação ambiental em um contexto de reciclagem de plástico no Brasil - Holanda, Lucas Nogueira (2022)
Environmental preservation will be one of the greatest challenges for humanity from the 21st century onwards, mainly due to the production of waste, especially plastic, which, despite the numerous uses it brings to human daily life, harms nature in several ways. The production of plastic needs to be discouraged and one of the most effective ways to do so is through economic instruments that encourage plastic recycling and make it advantageous compared to virgin plastic production, such as environmental taxation. Currently, in Brazil, there is a series of different systems for the recycled product compared to the virgin product, however, the currently existing legislation has dysfunctions that cause the achievement of an effect different from that intended by the legislator, as was found in the judgment of the Extraordinary Appeal No. 607.109. The objective of the research is to identify the possible dysfunctions in Brazilian taxation with regard to plastic so that environmental taxation can be used to increasingly encourage its recycling. In the course of the research, we sought to carry out a study of the bibliography of environmental taxation and of the reports that highlight the current context of plastic in Brazil and in the world. Then, a study of Brazilian legislation was carried out, aiming to identify possible dysfunctions and elaborate increments for the success of environmental taxation in encouraging plastic recycling. In the end, it was observed that, even after the changes resulting from the STF decision, the PIS/COFINS system still needs adjustments to make it more compatible with the Brazilian reality and the ICMS legislation needs to be unified in all states, in molds of state laws that attribute the same importance to the sale of products made from waste that they attach to the sale of waste itself. Furthermore, the emergence of complementary taxation strategies is welcome, which may arise even in the Tax Reform.